Appraising Forest-Based Livelihoods through Assessment of Major NTFPs: A Case Study from Jharkhand, India - Prasad, Sunil; Chauhan, Dhanpal Singh (International Journal of Economic Plants, 2020)
The state Jharkhand is one of the Non-Timber Forest Products (NTFPs) rich states of the country because of diverse physiographic and climatic conditions. It is known for its mineral wealth, tribal population and forests. NTFPs play an important role in supporting rural livelihoods and food security in tribal Jharkhand. The present study was carried out in three distinct villages of Jharkhand to explore the range of livelihood contributions of NTFPs. The study was based on empirical fieldwork using both quantitative and qualitative data. A structured interview schedule was managed for the respondents. Comparing income sources, we found that most of the households collect NTFPs and earn a handsome amount of income from NTFPs ranges from 33% to 59%. We also prioritized potential NTFPs along with their basic value chain.